Voltammetric Determination of Ivabradine Hydrochloride Using Multiwalled Carbon Nanotubes Modified Electrode in Presence of Sodium Dodecyl Sulfate - Ali Kamal Attia; Nisreen Farouk Abo-Talib; Marwa Hosny Tammam (Advanced Pharmaceutical Bulletin, 2017)
Purpose: A new sensitive sensor was fabricated for the determination of ivabradine hydrochloride (IH) based on modification with multiwalled carbon nanotubes using sodium dodecyl sulfate as micellar medium to increase the sensitivity.